ANALISIS PENGARUH FEAR OF MISSING OUT (FOMO) DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN PRODUK PADA PROMO VOUCHER TIKTOK SHOP DI KOTA PALANGKA RAYA (STUDI KASUS PADA ROTI’O LIPPO PLAZA) - Yosephin Damayanti Hutagalung, Ayesha; Tri Harinie, Luluk; Sukmani, Meylinda; Meitiana, Meitiana (Penerbit Lafadz Jaya, 2026)
The growth of social commerce through TikTok Shop has revolutionized the way people make purchases, largely due to psychological factors and lifestyles. This study explores the role of fear of missing out (FoMo) and lifestyle in influencing individual choices when purchasing Roti'O products using TikTok Shop vouchers in Palangka Raya. The research employed a quantitative survey approach. Data were collected from 96 individuals who had purchased Roti'O products using TikTok Shop vouchers. Data analysis was performed using multiple linear regression using SPSS. The results show that FoMo has a positive and significant influence on shopping decisions. Both FoMo and lifestyle together significantly impact shopping choices. These findings suggest that the pressure to stay on top of deals and lifestyles influenced by social media platforms are key factors driving people to shop. This research broadens the understanding of digital consumer behavior and provides valuable insights for marketing strategies in social commerce.